Concepts And Implementation Learning - Muhammad Yusuf; Amalia Syurgawi (THE JOER: Journal Of Education Research, 2021)
This paper aims to analyze the nature of learning and instruction and the components associated with instruction. This paper uses library research, that is by analyzing the sharing of literature. The results of the research show that learning is a process of changing behavior and understanding by being equipped with natural potential so that behavior and understanding will increase, while instruction is a learning process carried out by two actors, one as an educator and the other as a student. The components in the instruction are all aspects needed in learning such as teachers, students, objectives, materials, methods, tools, evaluations.